Climate Change Institutional Assessment - World Bank (World Bank, Washington, DC, 2021)
Climate change poses particularly difficult challenges for public sector institutions. Climate change impacts all sectors of the economy and society. Action to address climate change requires coordination among multiple government and nongovernment actors. The extended time frame over which climate change unfolds requires a capability to plan, implement, and sustain a credible commitment to increasingly ambitious policies over multiple political cycles. There will be winners and losers. Policies may be contested. The Climate Change Institutional Assessment (CCIA) identifies the strengths and weaknesses of the institutional framework for addressing these climate change governance challenges. The audience for the assessment is officials of center-of-government agencies responsible for policy, planning, and finance, agencies with leading roles in climate change policy, and inter-ministerial climate change bodies.